2010
DOI: 10.1007/s00442-010-1715-0
|View full text |Cite
|
Sign up to set email alerts
|

Fruit size decline from the margin to the center of capitula is the result of resource competition and architectural constraints

Abstract: Plants produce repeated structures, such as leaves, flowers, and fruits, which differ in size and shape. One example of this is fruit size, which is commonly observed to decrease from proximal to distal positions within an inflorescence. The resource limitation hypothesis proposes that because proximal fruits usually develop first, they have temporal priority on access to resources over distal fruits. The non-mutually exclusive architectural effects hypothesis suggests that these position effects in fruit size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 57 publications
1
26
0
4
Order By: Relevance
“…42, 43], it is likely that there would be a cost of increasing achene output in years of abundant pollinators in this species. As shown by Torices & Méndez [44] achenes within a capitulum can compete by resources, therefore, if fewer achenes compete by resources these may achieve a larger size. In a recent meta-analysis, García-Camacho & Totland [33] showed that although alpine plants suffer significant pollen limitation, there is no difference in pollen limitation between alpine and lowland species, and between self-compatible and self-incompatible species.…”
Section: Discussionmentioning
confidence: 97%
“…42, 43], it is likely that there would be a cost of increasing achene output in years of abundant pollinators in this species. As shown by Torices & Méndez [44] achenes within a capitulum can compete by resources, therefore, if fewer achenes compete by resources these may achieve a larger size. In a recent meta-analysis, García-Camacho & Totland [33] showed that although alpine plants suffer significant pollen limitation, there is no difference in pollen limitation between alpine and lowland species, and between self-compatible and self-incompatible species.…”
Section: Discussionmentioning
confidence: 97%
“…Besides variation in morphology, achenes may also vary markedly in size (Venable & al., 1987;McGinley, 1989;Maxwell & al., 1994;Imbert & al., 1996;Van Mölken & al., 2005;Brändel, 2007 ly the heaviest ones, whereas those adapted for greater dispersal are generally lighter (McEvoy, 1984;Tanowitz & al., 1987;Venable & al., 1987;Imbert & al., 1996;Imbert & Ronce, 2001;Brändel, 2004Brändel, , 2007Bastida & Menéndez, 2004, Bastida & al., 2010 among others). With regard to germination performance, recent research suggests that variation in achene size may be the main driver of divergent behavior exhibited by seeds from different achene morphs (Van Mölken & al., 2005;Torices & Méndez, 2010). Achene size can also affects performance in post-dispersal life-history traits, particularly in competitive conditions (McEvoy, 1984;Andersson, 1996;Ruiz de Clavijo & Jiménez, 1998;Meyer & Carlson, 2001;Ruiz de Clavijo, 2005;Van Mölken & al., 2005;Benard & Toft, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we found a proximal‐to‐distal decline in seed quantity and quality within inflorescences of S. trifolia , which was not caused by ovule limitation or decreases in quantity and quality of pollination on sequential flowers, thus rejecting the non‐uniform pollination hypothesis. The present study did not design an experiment to test whether the declining pattern was due to an architectural effect or resource competition, two independent and non‐mutually exclusive components of position effects (Lee ; Torices & Méndez ). However, two observations support the possibility of both.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, flowers within an inflorescence are not equal in some aspects, including floral organs, sex allocation, fruit and seed properties (Medrano et al . ; Diggle ; Guitián ; Buide ; Torices & Méndez ; Dai et al . ).…”
Section: Introductionmentioning
confidence: 99%